CHEMICAL, PHYSICAL-CHEMICAL PROPERTIES OF TYPICAL GRAY AND GRAY-GRAZING SOILS SPREAD IN THE CHIRCHIK-ANGREN BASIN (British Journal of Global Ecology and Sustainable Development, 2022)
The article provides information on the distribution of humus, common nutrients, carbonate content and distribution in fresh and old irrigated typical Burz and Burz-Meadow soils spread in Chirchiq - Angren Basin, depending on their composition.It was determined that these soils differ in their chemical composition, their composition depends on the deposits and homophysics. New data have been obtained on the capacity of soil absorption Complecs and the content of cations absorbed, their association with organic matter.